2003
DOI: 10.1046/j.1095-8649.2003.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequence divergence between two cryptic species of Lethenteron, with reference to an improved identification technique

Abstract: Genetic divergences and population structures were examined in the cryptic Lethenteron sp. N and sp. S, based on mitochondrial DNA (mtDNA) cytochrome oxidase subunit I (CO I) region sequences. An improved method of discrimination between L. sp. N and sp. S was found using PCR, with diagnostic primers for each species‐specific sequence in the mtDNA CO I region. Identification of 50 individuals of each species by this analysis was consistent with that by allozyme analysis of nuclear DNA. L. sp. N and sp. S, iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…Our results confirm the validity of subtle morphological characters for distinguishing species of the genus Tripterygion, and the existence of a cryptic species, as occurs in other fish taxa (Gleeson et al, 1999;Henriques et al, 2002;Yamazaki et al, 2003). Nevertheless, the criteria used to designate distinct species based on molecular data are always controversial (Cracraft, 1989;Avise, 1994).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our results confirm the validity of subtle morphological characters for distinguishing species of the genus Tripterygion, and the existence of a cryptic species, as occurs in other fish taxa (Gleeson et al, 1999;Henriques et al, 2002;Yamazaki et al, 2003). Nevertheless, the criteria used to designate distinct species based on molecular data are always controversial (Cracraft, 1989;Avise, 1994).…”
Section: Discussionsupporting
confidence: 71%
“…The genetic divergence between T. tripteronotus and T. tartessicum is 9.14% for COI, 5.32% for 12S and 6.72% for 16S, similar to the divergence observed between other fish taxa. Yamazaki et al (2003), using COI, found a sequence difference of 9.10±0.36% between two cryptic species of brook lamprey. For 16S, genetic distances between congeneric species of the families Soleidae, Mullidae and Apogonidae range between 4.6 and 11.70% (Tinti et al, 2000;Apostolidis et al, 2001;Mabuchi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…S coexist at every life stage, i.e., the larval, metamorphosed, and adult stages. Because these two species are diffi cult to differentiate on the basis of morphological characteristics (e.g., Yamazaki and Goto, 1997), genetic analysis based on mtDNA sequence-specifi c PCR was conducted according to Yamazaki et al (2003).…”
Section: Methodsmentioning
confidence: 99%
“…N and sp. S, sensu Yamazaki et al, 2003a) (Iwata et al, 1985;Yamazaki and Goto, 2000). Adult E. tridentatus are clearly distinct from any Lethenteron species, having a developed supraoral lamina with three sharp cusps and four series of lateral teeth on each side of the disc.…”
mentioning
confidence: 95%
“…Although lamprey species identifications have been recently carried out using genetic analyses, i.e., allozyme (Yamazaki and Goto, 1998;Yamazaki, 2002) and sequencespecific polymerase chain reaction (PCR) methods for mitochondrial DNA (mtDNA) (Yamazaki et al, 2003a), a T he Pacific lamprey Entosphenus tridentatus (Richardson) has a larval period of some 5 or 6 years, metamorphosed adults subsequently migrating downstream to the sea or large lakes, where they become parasitic feeders until migrating upstream for spawning (Scott and Crossman, 1973). This species is mainly distributed along the Pacific coast and off coastal islands of North America, from Unalaska Island in the Aleutians to Baja California (Scott and Crossman, 1973).…”
mentioning
confidence: 99%